2014
DOI: 10.1128/iai.01667-13
|View full text |Cite
|
Sign up to set email alerts
|

Aerobactin Mediates Virulence and Accounts for Increased Siderophore Production under Iron-Limiting Conditions by Hypervirulent (Hypermucoviscous) Klebsiella pneumoniae

Abstract: f Hypervirulent (hypermucoviscous) Klebsiella pneumoniae (hvKP) strains are an emerging variant of "classical" K. pneumoniae (cKP) that cause organ and life-threatening infection in healthy individuals. An understanding of hvKP-specific virulence mechanisms that enabled evolution from cKP is limited. Observations by our group and previously published molecular epidemiologic data led us to hypothesize that hvKP strains produced more siderophores than cKP strains and that this trait enhanced hvKP virulence. Quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
219
2
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(237 citation statements)
references
References 55 publications
(69 reference statements)
11
219
2
5
Order By: Relevance
“…Moreover, in Shigella flexneri, combined deletion of iucD and ferrous iron acquisition systems (feoB and/or sitA) leads to smaller plaque formation on Henle cell monolayers (65). A recent study also demonstrated that deletion of iucA in hypervirulent Klebsiella pneumoniae leads to less growth in human ascites fluid and to less virulence in mice (66).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in Shigella flexneri, combined deletion of iucD and ferrous iron acquisition systems (feoB and/or sitA) leads to smaller plaque formation on Henle cell monolayers (65). A recent study also demonstrated that deletion of iucA in hypervirulent Klebsiella pneumoniae leads to less growth in human ascites fluid and to less virulence in mice (66).…”
Section: Discussionmentioning
confidence: 99%
“…When considering these infections, it is important to recall that HV strains are far more likely to cause community-acquired and systemic infections in otherwise healthy individuals, but for the most part, these strains are geographically limited to Taiwan and Southeast Asia. In contrast, classical strains of K. pneumoniae typically cause serious nosocomial infections or UTIs and can be found worldwide (41,(48)(49)(50). While there is a broad overlap of the types of infections caused by classical versus HV strains, some diseases are far more likely to be caused by HV than classical strains.…”
Section: Infections Caused By K Pneumoniaementioning
confidence: 99%
“…Interestingly, while aerobactin is found only rarely in classical strains causing lung infection, it may be the predominant siderophore expressed in certain HV K. pneumoniae strains causing lung infection (331). HV K. pneumoniae strains have an increased ability to acquire iron through amplified siderophore production, and aerobactin makes up the vast majority of the total siderophores produced in at least one HV K. pneumoniae strain (49). Furthermore, one study found that aerobactin, but not enterobactin, yersiniabactin, or salmochelin, is needed for successful infection by HV K. pneumoniae in pneumonic and subcutaneous mouse infection models (49,331).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…2,10,11 Construction of in-frame deletion mutants in Serotype K20 and CPS gene exchange from serotype K1 to K20…”
Section: Detection Of Virulence Determinants For Hypervirulent Strainmentioning
confidence: 99%